The Families of the Chemical Heritage Foundation - Chemical Heritage Foundation (2000)
A promotional video celebrating the namesakes of spaces and programs at the Chemical Heritage Foundation (now the Science History Institute). This video was created for the opening of the Chemical Heritage Foundation's new location in Center City, Philadelphia in 2000.
Keywords: Dow, Herbert Henry, 1866-1930; Fisher, Chester G., 1881-1965; Gerstacker, Carl A., 1916-; Du Pont, Eleuthère Irénée, 1771-1834; Garfield, Eugene; Othmer, Donald F. (Donald Frederick), 1904-1995; Edelstein, Sidney M.; Beckman, Arnold O.; Chemical Heritage Foundation; Science museums